EVALUATION OF THE PERFORMANCE OF LOCAL SELF-GOVERNMENT BODIES IN THE PUBLIC MANAGEMENT SYSTEM (INNOVATIVE ECONOMY, 2023)
Onofriychuk D.M. EVALUATION OF THE PERFORMANCE OF LOCAL SELF-GOVERNMENT BODIES IN THE PUBLIC MANAGEMENT SYSTEMPurpose. The aim of the article is to substantiate the mechanism for evaluating the performance of local self-government bodies in accordance with modern challenges, functional load for the purpose of further implementation of the outlined approaches to the modernization of public management.Methods of research. The methods of historical, dialectical, monographic, systematic, comparative, structural analysis, abstract and logical generalization are used in the scientific publication. The institutional approach was focused on the study of interaction between public management and government institutions. The process approach involves evaluating the results of the provision of public services using international management quality criteria. The method of abstract and logical generalization made it possible to form conclusions and recommendations as a result of the research.Findings. The system of evaluating the effectiveness of the work of public institutes from the standpoint of scientific achievements and practical approaches has been analysed. Attention is paid to innovative approaches to evaluating the work of public institutions, which are based on monitoring performance, change management, achieving a balance between the target, economic, and functional components of the management activity of the local self-government body. The analysis of the management system of public institutions of the European Union and the implementation of this system in domestic practice is highlighted.Originality. It is suggested that in the management evaluation systems of public institutions, monitoring of the acquisition and use in functional activities by officials of the best practices of local development management, improvement of professional knowledge and skills in accordance with the challenges and needs of digitalization, decentralization, integration into the EU.Practical value. The conclusions and recommendations contained in the article have a theoretical basis and practical significance. The main provisions of the scientific article will contribute to the construction of an effective management system of local self-government bodies; will improve the effectiveness of their functional activities in conditions of volatility.Key words: evaluation of the public management system, evaluation criteria, European practice of evaluating the work of public institutions, capacity of local self-government bodies, innovative approach to evaluation.
Keywords: evaluation of the public management system; evaluation criteria; European practice of evaluating the work of public institutions; capacity of local self-government bodies; innovative approach to evaluation